LEGAL PROTECTION OF CONSUMER RIGHTS BASED ON ARTICLE 18 CONSUMER LAW PROTECTION AND THE IMPLEMENTATION OF BALANCE AND PROPORTIONALITY PRINCIPLES IN RAW CLAUSULA - Syafrida Syafrida; Ralang Hartati (Jurnal Hukum Replik, 2021)
In business or trading activities, business actors use standard contracts. Standard contracts or standard clauses are contracts whose contents are determined by the party having a stronger or dominant position. In business contracts, business actors have a stronger or more dominant position than consumers in determining the standard class substance unilaterally. Article 18 of Law Number 8 of 1999 regulates the prohibition of business actors conducting business activities, among others in the standard class, business actors rejecting risks, refusing refunds, taking unilateral actions on new or additional regulations, burdening consumers with guarantees of security rights. in sales. and installment purchases as if it has received approval from the consumer, arranging the proof in case of breach of promise. Business actors who violate Article 18 of the UK result in the classification of standards being null and void by law. The imbalance between business actors and consumers in standard contacts is against the principles of balance and proportionality. Therefore, in order for the standard classification made by actors not only to realize the interests of business actors but also the interests of consumers, business actors in making standard contracts must pay attention to the provisions of Article UUPK 18 and apply the principles of balance and proportionality.Keywords: Legal protection, consumer rights, standard clauses